2020
DOI: 10.1002/qj.3852
|View full text |Cite
|
Sign up to set email alerts
|

Weight structure of the Local Ensemble Transform Kalman Filter: A case with an intermediate atmospheric general circulation model

Abstract: The Local Ensemble Transform Kalman Filter (LETKF) computes analysis by using a weighted average of the first‐guess ensemble with surrounding observations within a localization cut‐off radius. Since overlapped observations are assimilated at neighbouring grid points, the LETKF results in spatially smooth weights. This study explores the spatial structure of the weights with the intermediate atmospheric model SPEEDY (Simplified Parameterizations, Primitive Equation Dynamics). Based on the characteristics of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

5
0

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 39 publications
2
11
0
Order By: Relevance
“…As seen in Figures 5b and f Ocean (Figure 11b), which was consistent with the findings of Kotsuki et al (2020) that the optimal localization scale was larger in sparsely observed regions compared to densely observed regions. By contrast, increasing only Le degraded the RMSEs over the tropics and in the Northern Hemisphere (Figure 11b), perhaps because the optimal localization scale for densely observed regions is smaller than that for sparsely observed regions (Kotsuki et al 2020). In addition, error covariance tends to be smaller over the Increasing only Lc had detrimental effects on RMSEs, especially in sparsely observed regions of the southern Pacific Ocean (Figure 11c).…”
Section: Impacts Of Applying Different Localization Scalessupporting
confidence: 90%
See 2 more Smart Citations
“…As seen in Figures 5b and f Ocean (Figure 11b), which was consistent with the findings of Kotsuki et al (2020) that the optimal localization scale was larger in sparsely observed regions compared to densely observed regions. By contrast, increasing only Le degraded the RMSEs over the tropics and in the Northern Hemisphere (Figure 11b), perhaps because the optimal localization scale for densely observed regions is smaller than that for sparsely observed regions (Kotsuki et al 2020). In addition, error covariance tends to be smaller over the Increasing only Lc had detrimental effects on RMSEs, especially in sparsely observed regions of the southern Pacific Ocean (Figure 11c).…”
Section: Impacts Of Applying Different Localization Scalessupporting
confidence: 90%
“…For the original LETKF implementation in SPEEDY based on Hunt et al (2007), the computational costs increased by O (m 3 ) due to the eigenvalue decomposition of (𝐏 ̃𝑎) −1 = 𝐈 + (𝐇𝐙 𝑏 ) 𝑇 𝐑 −1 𝐇𝐙 𝑏 (black lines of Figure 13), which was also observed for previous SPEEDY-LETKF experiments (cf. Table 2 of Kotsuki et al 2020). Figure 13 is consistent with our expectation that for large (m + c), the cost of the Optimal Eigen-Decomposition (OED) ETKF formulation would be proportional to O ((m + c) 2 ) and not…”
Section: Computational Costs As M+c Becomes Largesupporting
confidence: 85%
See 1 more Smart Citation
“…SPEEDY is a hydrostatic model with a primitive equation dynamics and simplified parameterizations that include essential processes such as convection, large‐scale condensation, longwave and shortwave radiation, and boundary layer turbulence. SPEEDY has been used to study atmospheric predictability (e.g., Abid et al., 2015; Bahaga et al., 2015; Ehsan et al., 2013) and has been used as a testbed for DA studies first by Miyoshi (2005) and a number of follow‐on studies (e.g., Amezcua et al., 2014; Greybush et al., 2011; Hatfield et al., 2018; Kalnay et al., 2007; Kondo & Miyoshi, 2016, 2019; Kotsuki et al., 2020; Li et al., 2009; Miyoshi, 2011; Miyoshi et al., 2014). We choose SPEEDY for its ability to represent realistic physics with a low computational cost.…”
Section: Methodsmentioning
confidence: 99%
“…It is important to note that, although the ensemble member 1 corresponds to the true state at the time we are initialising the ensemble, this is no longer valid after the first DA cycle. Using this initial ensemble, we used the LETKF to assimilate globally distributed radiosonde observations (Kotsuki et al ., 2020). However, to assimilate these observations using the LETKF, it is important to bear in mind that the implementation of ensemble Kalman filters in realistic frameworks (i.e., use of relative small ensemble members Ofalse(50false)) is characterised by two problems: forecast error covariance matrices (i) are rank deficient and (ii) contain spurious long‐distance correlations.…”
Section: Illustration Using Speedy‐letkf Global Da Modelmentioning
confidence: 99%